Perkembangan Jaringan Kerjasama Perpustakaan - Yusniah Yusniah; Rizki Febri Yanti; Dea Amanda; Fauzia Siregar (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
In order to realize library services that are carried out in an excellent and user-oriented manner, library collaboration is carried out. This library collaboration serves to provide wider access to collections, improve user and technical services, and increase activities in various resources. Technological developments have an impact on document products and the content of information contained in them varies. In addition to the library network, there is also an information network whose members do not limited to the library, but also information units outside the library such as documentation centers, data banks, information analysis centers, and referral centers. Here we discuss the UISU library collaboration network. Keywords: library collaboration, technological developments